Performance and Productivity in Banking and Capital Markets : an 'Emergent' Markets Perspective. - Ševic, Željko (Managerial Finance: Volume 36, Edition 12., 2010)
The issue looks at the performance of banking and financial markets within emerging economies, tackling a number of issues, such as, portfolio optimisation, banking productivity, management of interest rate margin, investment returns and finally, the investment and return on depository receipts (DR). The authors have dealt primarily with original datasets, combining secondary sources which are quite often supplemented by the results of their own primary data collection. The papers offer a fresh insight into the burning issues within the financial and banking markets in transitional/emerging ec.